Paviland Cave : contextualizing the 'Red Lady' - Aldhouse-Green, Stephen
Paviland is the richest Early Upper Palaeolithic site in the British Isles and has produced Britain's only ceremonial burial (the 'Red Lady') of that age. Excavations in the 19th and early 20th centuries, combined with the action of the sea, have removed virtually all of the cave's sedimentary sequence. A new, definitive study of the site and its finds, together with over 40 radiocarbon dates, shows that Paviland currently holds the key to our understanding of the chronology of human activity and settlement from c. 30,000 to 21,000 years ago. The age of the 'Red Lady' is also finally resolved at c. 26,000 b.p.